DEVELOPMENT OF A QUESTIONNAIRE TO ASSESS COVID-19 PREVENTION BEHAVIOR OF CLINICAL CLERKSHIP STUDENT IN FACULTY OF MEDICINE ANDALAS UNIVERSIT - Syafitri Ayu Asyifa; Yulistini -; Rima Semiarty (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
Background: During the Covid-19 pandemic, clinical clerkship students must understand good Covid-19 prevention behavior because they have been directly contacting health workers and patients in hospitals. However, until now, there has been no research on Covid-19 prevention behavior aimed at clinical clerkship students in Indonesia. The use of a questionnaire that has been tested for validity and reliability is necessary.Objective: The purpose of this study was to develop a questionnaire about Covid-19 prevention behavior in clinical clerkship students.Methods: This study is a descriptive study with a cross-sectional design. The sampling technique used consecutive sampling with a sample size of 45 students of clinical clerkships in the medical profession, Faculty of Medicine, Andalas University.Results: The validity test was carried out with a qualitative and quantitative approach to experts and test respondents. The final result of the content validity of two rounds of the Content Validity Index (CVI) is 1.00, so the questionnaire is valid with 33 question items. The reliability of the knowledge section measured with Kuder Richarson-21 was 0,888, while in the attitude and practice section, using the alpha coefficient formula, were 0.682 and 0.8816, respectively.Conslusion: The developed questionnaire was declared valid and reliable. This questionnaire can be used to measure Covid-19 prevention behavior in clinical clerkship students.